1983
DOI: 10.1042/cs0650561
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis, Bodily Renewal and the Sleep-Wake Cycle

Abstract: 2. Bullough. W.S. (1948) Mitotic activity in the adult male mouse Mus niusculrrs L. The diurnal cycles and theL relations to waking and sleeping. I?acredhw oJ'rlic Royal Sociery. Series B, 135,212-233. 3. Halbcrg, I:., Zandcr. H.A., Houglum, M.W. k Miihlemann. H.R. (1954) Daily variations in tissue mitoses, blood eosinophilr and rectal temperatures of rats. American Journal of Physiology. 111, 361-366. 4. Halberg. C., Calicich. J.H., Ungar, C. k French, L.A. (1965) Ckcadian rhythmic pituitary adrenocorticotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(69 citation statements)
references
References 59 publications
4
63
0
2
Order By: Relevance
“…Visual feedback for pedal frequency, power output and elapsed time were provided. All strength and/or endurance based exercise commenced at the same time of day (0900 h ± 1h) to avoid any diurnal performance or signalling variations 25 .…”
Section: Figure 1 About Herementioning
confidence: 99%
“…Visual feedback for pedal frequency, power output and elapsed time were provided. All strength and/or endurance based exercise commenced at the same time of day (0900 h ± 1h) to avoid any diurnal performance or signalling variations 25 .…”
Section: Figure 1 About Herementioning
confidence: 99%
“…The restorative theory considers brain activity during sleep essential to restore body and mind [8,9]. As non restorative sleep is common in patients with organic sleep disorders, it has been considered a symptom of insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that higher energy expenditure during the day is associated with energy conservation and tissue restoration during sleep [11,12,13], whilst the exercise-induced increase in core body temperature may activate sleep-associated heat-loss mechanisms (see [13] for an overview). In addition, physical exercise has been shown to have a positive influence on longer sleep duration [14,15,16].…”
Section: Introductionmentioning
confidence: 99%